PERAN ELCP DALAM MENGEMBANGKAN PROGRAM BAHASA INGGRIS UNTUK PENCAPAIAN STANDAR ‘WORLD CLASS UNIVERSITY’ - Satrya, I Gusti Bagus Honor (E-Jurnal Manajemen, 2017)
This research tries to discover the effects of the development and the implementation of undertaking an English Language Class Program (ELCP) at the Faculty of Economics and Business in Udayana University in order to achive the level of a ‘World Class University’ through good management of education at the university level and faculty level. The sample that will be utilised for the this research will be from the current ELCP regular program at the bachelor level students from years 2015 and 2016 in which are made up of three disticnt concentrations which are: Management, Accounting and Economics Studies. The sample size that will be used to show the correlation of the ELCP program in the achievement of the ‘World Class University’ standard will be 93 recipients. The data gathering is done through undertaking questionaires and obsrvations of all students that are currently undergoing the ELCP program. This research will be using the ‘Likert 5 (five) points method in the measurement of the thirty four (34) questions within the questionaire. The analysis that will be conducted will be using a ‘Descriptive’ technic. The result of this analysis is to show the role of the ELCP program that effects positively the achievement of the standard of ‘World Class University. Furthermore, it will be possible to indicate that ELCP should be further developed at the faculty level dan also at the university level in which can create positive competitiveness for Udayana University at the national level and also the International level.